Comparison of lens refractive parameters in myopic and hyperopic eyes of 6–12-year-old children - Shang, Jianming; Hua, Yanjun; Wang, Yuliang; He, Ji C.; Zhou, Xingtao; Qu, Xiaomei (Frontiers in Medicine, 2022)
Background/Aims: To evaluate the influence of cycloplegia on lens refractive parameters in 6–12-year-old children with myopia and hyperopia for exploring the pathogenesis of myopia. Methods: One hundred eyes of 100 patients (50 boys) were included. In the myopic group, 50 subjects (25 boys and 25 right eyes) were enrolled with a mean age of 9.20±1.69 years. IOLMaster 700 measurements were performed pre- and post-cycloplegia. The pictures were marked using semi-automatic software. The lens curvature and power were obtained using MATLAB image processing software. Paired and independent sample t-tests were used for data analysis. Statistical significance was set at P < 0.05. Results: Anterior and posterior lens curvature radius in myopic eyes were larger than those in hyperopic eyes, both pre- and post-cycloplegia (both P<0.001). The refractive power in myopic eyes was lower than that in hyperopic eyes without cycloplegia, both pre- and post-cycloplegia (both P<0.001). The changes in anterior lens curvature and refractive power between pre- and post-cycloplegia in hyperopic eyes were larger than those in myopic eyes (both P<0.05). No significant difference was found in the change in posterior lens curvature and refractive power after cycloplegia in hyperopic and myopic eyes (P > 0.05). Conclusions: Anterior and posterior surfaces of the lens were flatter, and the refractive power was lower in the myopia group than in the hyperopia group. Myopic and hyperopic patients showed a tendency for lens flattening and refractive power decrease after cycloplegia. Hyperopic patients had more changes in anterior lens curvature and refractive power after cycloplegia.